A new species of the booklouse genus Embidopsocus in Baltic amber (Psocoptera: Liposcelididae) - Engel, Michael S. (Novitates Paleoentomologicae, 2016)
The first representative of the booklouse genus Embidopsocus Hagen (Nanopsocetae: Liposcelididae) is documented from the blaue Erde of northern Europe. Embidopsocus pankowskiorum Engel, new species, is similar to the related E. saxonicus Günther from the Bitterfeld deposits (so-called ‘Saxonian amber’) and E. eocenicus Nel et al. from Oise amber, but differs in details of antennal structure, setation, wing venation, and size. The species is described and comments made regarding its character affinities to other fossil liposcelidids.